2021
DOI: 10.1002/adma.202105135
|View full text |Cite
|
Sign up to set email alerts
|

Dual‐Single‐Atom Tailoring with Bifunctional Integration for High‐Performance CO2 Photoreduction

Abstract: Single‐atom photocatalysis has been demonstrated as a novel strategy to promote heterogeneous reactions. There is a diversity of monoatomic metal species with specific functions; however, integrating representative merits into dual‐single‐atoms and regulating cooperative photocatalysis remain a pressing challenge. For dual‐single‐atom catalysts, enhanced photocatalytic activity would be realized through integrating bifunctional properties and tuning the synergistic effect. Herein, dual‐single‐atoms supported o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
154
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 237 publications
(172 citation statements)
references
References 78 publications
(99 reference statements)
3
154
0
Order By: Relevance
“…[149] In recent years, SACs have large metal utilization rate and highly density active sites and show excellent performance in many important catalytic reactions, which also provide a favorable research basis for exploring new AFC materials for photocatalytic CO 2 reduction reaction (see Table 3). [52,57,[150][151][152][153][154][155] Recently, Ma et al [150] proposed a pyrolysis-induced vaporization strategy to fabricate ultrahigh-density Co 1 /g-C 3 N 4 SACs with a record metal loading of 24.6 wt%, which revealed remarkable activity and selectivity for photocatalytic CO 2 reduction to CH 3 OH in the absence of both sacrificial reagent and photosensitizer (see Figure 15A-C). The Co single atoms were prepared by the pyrolysis-induced vaporization process in a two-step calcination procedure.…”
Section: Photocatalytic Co 2 Reduction Reactionmentioning
confidence: 99%
See 2 more Smart Citations
“…[149] In recent years, SACs have large metal utilization rate and highly density active sites and show excellent performance in many important catalytic reactions, which also provide a favorable research basis for exploring new AFC materials for photocatalytic CO 2 reduction reaction (see Table 3). [52,57,[150][151][152][153][154][155] Recently, Ma et al [150] proposed a pyrolysis-induced vaporization strategy to fabricate ultrahigh-density Co 1 /g-C 3 N 4 SACs with a record metal loading of 24.6 wt%, which revealed remarkable activity and selectivity for photocatalytic CO 2 reduction to CH 3 OH in the absence of both sacrificial reagent and photosensitizer (see Figure 15A-C). The Co single atoms were prepared by the pyrolysis-induced vaporization process in a two-step calcination procedure.…”
Section: Photocatalytic Co 2 Reduction Reactionmentioning
confidence: 99%
“…In addition to polymer carbon nitride semiconductors [57,[150][151][152][153][154][155] and MOF [52] supports, metal compound semiconductor-based supports have also been used to design SAC for photocatalytic CO 2 reduction. [160,161] For example, Zhou et al lately reported a novel concept of interfacial electron concentration regulation in Au 1 -modified CdS support (Au 1 /CdS), which for the first time realized electron enrichment at Cd cationic vacancy sites rather than Au atomic sites.…”
Section: Photocatalytic Co 2 Reduction Reactionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, photocatalytic CO 2 methanation is also able to mitigate the increasing CO 2 concentration in the atmosphere. Nevertheless, complex CO 2 photoreduction processes often lead to a wide range of possible products, [10][11][12][13][14] and the effective photoreduction of CO 2 into CH 4 remains a huge challenge.…”
mentioning
confidence: 99%
“…With the rapid development of industry, large numbers of organic pollutants are misused in the various fields of life, which brings serious environmental problems [1][2][3][4] . It is well known that semiconductor photocatalytic technology is an eco-friendly and valid way to degrade and remove the typical contaminants, and photocatalyst plays a key role in the application of this technology [5][6][7][8] . Thus, the various semiconductor materials have been used in the field of pollutants removal.…”
mentioning
confidence: 99%